Case report: Two unique cases of co-existing primary brain tumors of glial origin in opposite hemispheres - Singhal, Ishan; Coss, Dylan; Mueller, Wade; Straza, Michael; Krucoff, Max Ostrinsky; Santos-Pinheiro, Fernando (Frontiers in Oncology, 2022)
Background: Primary CNS tumors are rare. Coexistence of two glial tumors of different histological origins in the same patient is even rarer. Here we describe two unique cases of coexisting distinct glial tumors in opposite hemispheres. Cases: Patient 1 is a 38-year-old male who presented with a seizure in February/2016. MRI showed a left parietal and a right frontal infiltrating nonenhancing lesions. Both lesions were resected revealing an oligodendroglioma WHO grade-2 and an astrocytoma WHO grade-2. Patient 2 is a 34-year-old male who presented with a seizure in November/2021. MRI showed a left frontal and a right mesial temporal lobe infiltrating nonenhancing lesions. Both lesions were resected revealing an oligodendroglioma WHO grade-2 and a diffuse low-grade glioma, MAPK pathway-altered (BRAF V600E-mutant). Both patients underwent adjuvant treatment to one or both lesions, without recurrence to date. Discussion: Two histologically distinct glial tumors may coexist, especially when they are non-contiguous. Pathological confirmation of each lesion is imperative for appropriate management. We highlight the different management of gliomas based on the new CNS WHO 2021 classification compared to its 2016 version, based on NCCN guidelines. Although more molecular markers are being incorporated into glioma classification, their clinical impact of it is yet to be determined.